Auswirkungen von Hitze auf die Versorgung in zentralen Notaufnahmen im urbanen Raum - Anna-Lea Baumgärtner (2024)
Context: Heat events are, among other effects, direct consequences of climate change and global warming. In 2022 over 60,000 heat-related deaths were reported, and July 2023 has been the hottest month on record until today. In the future, heat events will increase, and the effects will be seen not only in the environment but also in people's health. This review aims to answer the question, what impact heat events have on people's health and care in central emergency departments in urban areas. Methods: This review consists of a theory-driven paper based on a literature review. In addition, it includes content on the current situation about heat events in Germany and aspects from three expert interviews. Results: Initially, heat events have significant effects on people's health. The heat island effect also amplifies this. Furthermore, emergency departments are directly related to people's health. As soon as the health is affected, heat events also influence care in emergency departments. Conclusion: The results underscore that resilience strategies to heat events must be established, first, preventively for the population and, second, for emergency departments to protect health and maintain care. Further work and studies can build on this foundation to strengthen and establish resilience in emergency departments to heat events.